2016
DOI: 10.5539/gjhs.v8n10p151
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Status and Related Factors among Middle-Aged Women in West of Iran, Hamadan: A Cross-Sectional Study

Abstract: Physical inactivity is a major health problem in developing countries. Regular Physical Activity (RPA) can reduce the risk of many diseases such as cardiovascular disease, diabetes, and obesity that are prevalent in middle and old ages specifically in women. The (RPA) status among middle-aged Iranian women is not well known. The purpose of this study was to investigate the physical activity status and related factors among middle-aged women in Hamadan, a city in western Iran. The participants of this cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(25 reference statements)
2
3
1
Order By: Relevance
“…Moreover, participants aged 35 to 44 demonstrated the least amount of insufficient PA, whereas those 75 years of age and older depicted the greatest levels. Consistent with previous studies, there is an inverse relationship between age and low PA, which has been identified as a significant determinant of PA [ 30 33 ]. Apparently, with increasing age, older people seem to be less motivated to be physically active and prefer quiet activities.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, participants aged 35 to 44 demonstrated the least amount of insufficient PA, whereas those 75 years of age and older depicted the greatest levels. Consistent with previous studies, there is an inverse relationship between age and low PA, which has been identified as a significant determinant of PA [ 30 33 ]. Apparently, with increasing age, older people seem to be less motivated to be physically active and prefer quiet activities.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were also found in a study with a population with chronic obstructive pulmonary disease, where higher self-efficacy at baseline predicted a positive response in a six-minute walk test [38]. Another study among middle-aged women also found that self-efficacy was an important predictor for physical activity [39]. As baseline self-efficacy appears to be an important predictor of physical activity, the importance of support to improve self-efficacy at the beginning of an intervention is emphasised.…”
Section: Discussionsupporting
confidence: 80%
“…Part of this has to do with the lack of culturalization for physical activity in Iranian people. Numerous articles support this topic Extensive epidemiological studies in Iranians confirm this (20)(21)(22). It seems that some patients with diabetes suffer from other concomitant diseases, such as heart disease and osteoarthritis and think that they are not capable of effective physical activity.…”
Section: Discussionmentioning
confidence: 89%